Mutations in RSPH1 cause primary ciliary dyskinesia with a unique clinical and ciliary phenotype. - Knowles, Michael R; Ostrowski, Lawrence E; Leigh, Margaret W; Sears, Patrick R; Davis, Stephanie D; Wolf, Whitney E; Hazucha, Milan J; Carson, Johnny L; Olivier, Kenneth N; Sagel, Scott D; Rosenfeld, Margaret; Ferkol, Thomas W; et al. (Am J Respir Crit Care Med, 2014)
RATIONALE: Primary ciliary dyskinesia (PCD) is a genetically heterogeneous recessive disorder of motile cilia, but the genetic cause is not defined for all patients with PCD. OBJECTIVES: To identify disease-causing mutations in novel genes, we performed exome sequencing, follow-up characterization, mutation scanning, and genotype-phenotype studies in patients with PCD. METHODS: Whole-exome sequencing was performed using NimbleGen capture and Illumina HiSeq sequencing. Sanger-based sequencing was used for mutation scanning, validation, and segregation analysis. MEASUREMENTS AND MAIN RESULTS: We performed exome sequencing on an affected sib-pair with normal ultrastructure in more than 85% of cilia. A homozygous splice-site mutation was detected in RSPH1 in both siblings; parents were carriers. Screening RSPH1 in 413 unrelated probands, including 325 with PCD and 88 with idiopathic bronchiectasis, revealed biallelic loss-of-function mutations in nine additional probands. Five affected siblings of probands in RSPH1 families harbored the familial mutations. The 16 individuals with RSPH1 mutations had some features of PCD; however, nasal nitric oxide levels were higher than in patients with PCD with other gene mutations (98.3 vs. 20.7 nl/min; P < 0.0003). Additionally, individuals with RSPH1 mutations had a lower prevalence (8 of 16) of neonatal respiratory distress, and later onset of daily wet cough than typical for PCD, and better lung function (FEV1), compared with 75 age- and sex-matched PCD cases (73.0 vs. 61.8, FEV1 % predicted; P = 0.043). Cilia from individuals with RSPH1 mutations had normal beat frequency (6.1 ± Hz at 25°C), but an abnormal, circular beat pattern. CONCLUSIONS: The milder clinical disease and higher nasal nitric oxide in individuals with biallelic mutations in RSPH1 provides evidence of a unique genotype-phenotype relationship in PCD, and suggests that mutations in RSPH1 may be associated with residual ciliary function.
Keywords: Adolescent; Adult; Child; Cilia; DNA Mutational Analysis; DNA-Binding Proteins; Exome; Female; Genetic Association Studies; Genetic Markers; Genetic Testing; Homozygote; Humans; Kartagener Syndrome; Linear Models; Male; Middle Aged; Mutation; Nasal Mucosa; Sequence Analysis, DNA; Young Adult